UPAYA MENCEGAH PAHAM RADIKAL DAN INTOLERANSI MELALUI WORKSHOP PENERJEMAHAN NASH KEAGAMAAN BAGI PARA DA’I DI KABUPATEN SUBANG - Asep Sopian; Mad Ali (LP2M Universitas Ibrahimy, 2019)
There are still plenty of radicalism and intolerance in Indonesia, like suicide bombing, Bali bombing, police station attacks and so on. The Managing Director of Wahid Institutes, Yenny Wahid (2017) said that the survey's results show that there is an increase in radical understanding in Indonesia, numbering 600,000 or 0.4 percent of Indonesia's population. A misinterpretation of religious texts and particularly those concerning the theme of jihad is a contributing factor. The method of service is conducted through workshops and seminars. After the priests took part, they gained new positive insights into the spread of Pesantren deradicalization and tolerance.